Clinical and personal characteristics in patients with metabolic syndrome of a primary care center - Agama-Benavides, Annabelí (2020)
Objective. To determine the clinical and personal characteristics of the metabolic syndrome (MS) in insured patients attached to the ESSALUD Assistance Network (Social Health Insurance) in Tambo, Huancayo. Methods. Descriptive, observational and retrospective study, conducted from January to October 2015. 101 patients participated using inclusion criteria: age between 18 and 60 years, meeting 3 of the 5 criteria of MS according to the International Diabetes Federation (IDF) 2009 and Association Latinoamericana de Diabetes (ALAD), complete medical records and surveys, and exclusion criteria: having a previous disease such as diabetes and high blood pressure. Results. The frequency of SM was 14.98 %. 62.4 % were women and the mean age was 47 y 51 years. 66.4 % comes from the urban area. 54.5 % were classifed as overweight and 23.6 % with grade I obesity. The mean abdominal circumference in women was 98.63 cm and for men 100.66 cm. 68.3 % had glycemic controls greater than 100 m / dl. The mean cholesterol and triglycerides were 234.26 mg / dL and 251.94 mg/ dL respectively. 51.5 % of the surveyed patients do not have an adequate level of knowledge of cardiovascular risk factors, 69.3 % have inadequate lifestyles and 58.41 % report having a low level of stress. Conclusions. The frequency of MS is low, predominantly in the female sex, being overweight and obesity the most prevalent factors, and it is related to inadequate lifestyles